Hirnantian Isotope Carbon Excursion in Gorny Altai, southwestern Siberia - Nikolay V. Sennikov; Leho Ainsaar; Tõnu Meidla (Estonian Journal of Earth Sciences, 2015)
The Hirnantian Isotope Carbon Excursion (HICE), a glaciation-induced positive δ13C shift in the end-Ordovician successions, has been widely used in chemostratigraphic correlation of the Ordovician–Silurian boundary beds in many areas of the world. However, large regions with Ordovician sediments in Siberia are almost unstudied for stable isotope chemostratigraphy. The Burovlyanka section in the Altai area is one of the rare Hirnantian–Rhuddanian sections with both carbonates and graptolitiferous shales occurring in the succession. Here we report the discovery of the HICE in the uppermost beds of the Tekhten¢ Formation, the Dalmanitina Beds in the Burovlyanka section. The Dalmanitina limestone Member between the graptolitiferous shales may correspond to the mid-Hirnantian glacial episode, which led to a global sea level drop and major extinction of marine fauna.